Principales hipótesis sobre la crisis financiera internacional - Oscategui, José (Economia, 2015)
This paper discusses the analytical arguments used to explain the international financial crisis thatbroke out in 2007. First, we stress Ben Bernanke’s global saving glut hypothesis, which holds that the causes of the financial instability in the USA were exogenous and primarily triggered by the actions of developing countries, the effects of which escaped the control of the American financial and monetary authorities. We then review the criticism of this hypothesis and the correction that Bernake himself applied, which admits, as being foremost, the existence of factors other than the actions of developing countries. Below, we present the theory of credit development and regulatory failures, which includes the unprecedented growth in credit and financial leverage amid increasing financial deregulation. Finally, we review the central ideas of Hyman Minsky, which stress the systemic nature of the crisis in the capitalist economy.The theory of credit development and regulatory failures strikes us as the most fitting, as the evidence in its favor is substantial; what is more, Bernanke amended his initial approach and incorporated elements of this hypothesis. The recent study by Reinhart and Rogoff (2009) isconsiderably broader, analyzing several centuries of crisis and allowing the recent crisis to be reconciled with the credit development and regulatory failures theory.